Protective Role of Thymoquinone Against TCE-Induced Liver Damage Through HSP70 Modulation - Gunes, Arzu; Colakoglu, Neriman (Wiley, 2026)
Trichloroethylene (TCE) is a widely used industrial solvent and a common environmental pollutant. Prolonged or high-dose exposure to TCE has been associated with oxidative stress, hepatotoxicity, and carcinogenesis. Accordingly, identifying compounds capable of preventing or attenuating TCE-induced hepatotoxicity has become increasingly important. Thymoquinone (TQ), a bioactive compound derived from Nigella sativa, exhibits potent antioxidant, anti-inflammatory, and hepatoprotective properties. This study aimed to investigate the protective effects of TQ against TCE-induced liver injury. Twenty-five male Wistar-Albino rats were randomly assigned to five groups: Control, TCE, TCE + TQ, TQ, and DMSO. Liver tissues were harvested, processed for histopathological evaluation, and analyzed for Heat Shock Protein 70 (HSP70) immunoreactivity. TCE exposure resulted in significant histopathological alterations, including vascular congestion, necrosis, inflammation, and sinusoidal dilatation. Moreover, TCE exposure caused a marked increase in HSP70 immunoreactivity (p < 0.05) compared with the control group. In contrast, TQ treatment alleviated these histopathological alterations and significantly reduced HSP70 immunoreactivity compared with the TCE group (p < 0.05), indicating attenuation of hepatic cellular injury. These findings suggest that TQ may exert hepatoprotective effects against TCE-induced liver injury and support further investigation of its potential role in mitigating environmentally induced hepatotoxicity.
Keywords: Hepatotoxicity; Hsp70; Inflammation; Thymoquinone; Trichloroethylene